Cortical signature related to psychometric properties of pain vigilance in healthy individuals: A voxel-based morphometric study. (16th February 2022) - Nagasaka, Kazuaki; Otsuru, Naofumi; Sato, Rui; Watanabe, Hiraku; Sakurai, Noriko; Ohno, Ken; Kodama, Naoki; Onishi, Hideaki
Highlights: PVAQ can evaluate two aspects of pain vigilance in non-clinical samples. We evaluated attention to pain and attention to changes in pain. Volume in left AIC was negatively correlated with attention to pain score. No brain region was correlated with attention to changes in pain score. Two psychological properties may involve different brain structure features. Abstract: The Pain Vigilance and Awareness Questionnaire (PVAQ) is a questionnaire for non-clinical and clinical cases of patients, such as those suffering from chronic pain. Moreover, it is used for evaluation of two aspects of habitual attention to pain: attention to pain and attention to changes in pain. As the PVAQ assesses two different aspects of attention function, different neural basis may present. However, it remains unclear which brain regions are involved. Here, we performed voxel-based morphometry (VBM) in 30 healthy participants to determine the regional morphology associated with the two attention states. Multiple regression analysis was conducted between each score and the regional grey matter (GM) volume, which revealed that a decreased GM volume in the left anterior insular cortex (AIC) was associated with a higher attention to pain score. In contrast, no brain region was correlated with the attention to changes in pain score. Our VBM results demonstrate that attention to pain scores assessed by PVAQ are associated with morphological features of the left AIC. Moreover, they may contribute to the elucidation of the complex psychological and neurophysiological characteristics of patients with chronic pain.